Spatiotemporal heterogeneity of malnutrition indicators in children under 5 years of age in Bangladesh, 1999–2011 - Hasan, Md Tanvir; Mamun, Abdullah A; Williams, Gail M; Soares Magalhães, Ricardo J (Cambridge University Press, 2022)
This article was published in the Public Health Nutrition [© The Authors 2018 ] and the definite version is available at : https://doi.org/10.1017/S136898001700341X The Journal's website is at: https://www.cambridge.org/core/journals/public-health-nutrition/article/spatiotemporal-heterogeneity-of-malnutrition-indicators-in-children-under-5-years-of-age-in-bangladesh-19992011/5A2899EB3F0499F0E944E9B2E5351BAD